Exploring the Macroscopic Properties of Humic Substances Using Modeling and Molecular Simulations - Yerko Escalona; Drazen Petrov; Edgar Galicia-Andrés; Chris Oostenbrink (Agronomy, 2023)
Soil organic matter (SOM) is composed of a complex and heterogeneous mixture of organic compounds, which poses a challenge in understanding it on an atomistic level. Based on the progress of molecular dynamics simulations and our efforts to create molecular systems that resemble SOM, in this work, we expanded our knowledge of SOM through the use of humic substances (HSs). Specifically, we studied the standardized samples of HS of the International Humic Substances Society (IHSS). This society provided the elemental and organic composition used as input parameters for our Vienna Soil Organic Matter Modeler 2 (VSOMM2). We modeled and simulated different HS samples from various sources, including soil, peat, leonardite, and blackwater river. In order to compare between different HS, we reduced the organic composition information to two principal components, which are associated principally with the amount of carboxyl and aromatic groups in the HS, denominated as PC<semantics>acid</semantics> and PC<semantics>arom</semantics>, respectively. We performed a plethora of analyses to characterize the structure and dynamics of the systems, including the total potential energy, density, diffusion, preferential solvation, hydrogen bonds, and salt bridges. In general terms, at the water content value of 0.2, we observed that most properties depend on the carboxyl group protonation state. The Coulombic interactions from this ionic specie and the interaction with cations determine the overall behavior of the studied systems. Furthermore, the type of cations and the pH influence those properties. This study exemplifies the importance of molecular dynamics to explain macroscopic properties from the structure and dynamics of the molecules modeled, such as the interaction network, i.e., hydrogen bonds or salt bridges of molecules presented in the system and their mobility.